EFEKTIFITAS SENAM JANTUNG SEHAT DAN SENAM ERGONOMIK KOMBINASI RELAKSASI NAFAS DALAM TERHADAP TEKANAN DARAH PADA PENDERITA HIPERTENSI PRIMER - Mayani ' Syahfitri; Safri ' '; Jumaini ' ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Hypertension is one of the continous abnormal blood pressure increase in artery vein for more than one period. This study aims to find the effect of healthy heart gymnastic and ergonomic gymnastic combined with deep breathing relaxation effectiveness toward the blood pressure of primary hipertension patients. The method used in this study was quasy experiment with pre test and post test design. The study was conducted in the working area of the Community Health Center of Harapan Raya. The number of samples used were 32 people which are divided into two groups 16 people as the healthy heart gymnastic and 16 people as the ergonomic gymnastic combined with deep breathing relaxation. The sampling method used was purposive sampling while keeping the inclusion criteria on mind. The measurement instrument used were digital sphygmomanometer and observation sheet. The analyses used were univariate and bivariate analysis with dependent t test. The result of the study indicated that heart gymnastic and ergonomic gymnastic combined with deep breathing relaxation may affect the blood pressure of primary hypertension patients with p value of 0.000 (p<0.005). for both groups. The average decrease of systolic blood pressure was 10.188 mmHg and diastolic was 8.313 mmHg for healthy heart gymnastic while the average decrease of systolic blood pressure was 16.875 mmHg and diastolic was 12.688 mmHg for ergonomic gymnastic combined deep breathing relaxation. Based on the result of the study, healthy heart gymnastic and ergonomic gymnastic combined deep breathing relaxation are recommended to be used to lower blood pressure. Keywords: Blood pressure, deep breathing relaxation, ergonomic exercises, healthy heart gymnastic exercises, primary hypertension